Persepsi Penyuluh Terhadap Pentingnya Peran Penyuluhan Perkebunan Kelapa Sawit di Kecamatan Xiii Koto Kampar Kabupaten Kampar - Fauzi Rizky Harahap; Rosnita '; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purposes of this research is to determind the organizing of extension oil palm plantations and to determind the agricultural extension field perceptions for importance the role of extension oil palm plantations. The method taked of data used is a survey method. Intake of respondents in this study conducted with purposive sampling with consideration of agricultural extention field with civil servants status in the agricultural extension center model in XIII Koto Kampar District with total six respondents. Data were analyzed with descriptive analyzed method of Likert's Summated Rating Scale. Variables this research are the role of extension sourch Mardikanto (2009) and Law No. 16 of 2006 of nine sub-variables. The result illustrate that organizing of extension in XIII Koto Kampar District has gone well according the elements of extension. The agricultural extension field perceptions describe the role of extension are "important" with a score of 3.92,  this can be seen from the sub-variables: (1) Facilitating the learning process is “important” with a score of 3.92; (2) Ease of acces is “important” with a score of 4.02; (3) Leadership ability is “important” with a score of 3.96; (4) Developing the organization is “important” with a score of 4.00; (5) Analyzing and solving problems is “important” with a score of 3.97; (6) Developing awareness is “important” with a score of 3.71; (7) Institutionalizing the cultural values is “important” with a score of 3.80; (8) Supervision or guidance is “important” with a score of 4.17; and (9) Evaluation is “important” with a score of 3.78.   Keywords: agricultural extension field perceptions, the importance of role extension, and oil palm plantations.